FARMER'S PARTICIPATION RATE IN DESA PEDULI GAMBUT PROGRAM - Lilis Handayani; Erlinda Yurisinthae; Wanti Fitrianti (Agricultural Socio-Economics Journal, 2022)
Many factors destroy peat ecosystems, including land fires. The cause of the fire was motivated by economic aspects, namely land clearing for agricultural, plantation, and residential activities. Desa Peduli Gambut Program has main activities: strengthening local knowledge and village community preparedness in dealing with peat fire disasters and non-burning land management. The process requires the participation of farmers as an essential determining factor to ensure the success and sustainability of a program. This study analyzes farmer participation in the DPG program in Teluk Pekedai District. The descriptive quantitative method is supported by qualitative data using Sherry Arnstein's (1969) participation level analysis. The analysis results show that farmer participation in the DPG program in Teluk Pekedai District is at the therapy level. The low level of community participation in a program occurs because the level of government domination in deciding program plans is the cause of problems in program implementation. Farmer participation can increase by the role of the DPG chairperson, the role of the village facilitator, the village government and local government, and all elements of the community (community leaders).